Epoxidation of cyclopentene by a low cost and environmentally friendly bicarbonate/peroxide/manganese system - Beatriz Hincapie; Sandra M Llano; Hector F Garces; Diego Espinal; Steven L Suib; Luis J Garces (Adsorption Science & Technology, 2018)
The system hydrogen peroxide/sodium bicarbonate/manganese sulfate was used for the first time to epoxidize cyclopentene. Effects of parameters such as type and amount of solvent, ratio of hydrogen peroxide and manganese sulfate to cyclopentene, presence of additives, and reaction time and temperature on the selectivity to cyclopentene oxide were evaluated. Gas chromatography was used to quantify residual cyclopentene and produced cyclopentene oxide using the internal standard method. Type and amount of solvent, addition method, and temperature were important factors to increase the selectivity to cyclopentene oxide. Unlike previous reports on epoxidation of different substrates, additives like sodium acetate and salicylic acid did not improve the selectivity to cyclopentene oxide. One time, single-step addition of hydrogen peroxide/sodium bicarbonate to the solution of cyclopentene/solvent/manganese sulfate produced more cyclopentene oxide than stepwise addition. The maximum selectivity obtained was 56%, possibly due to the high reactivity of cyclopentene that causes the formation of oxidation products different to cyclopentene oxide, which were not detected in the analyzed phase.